Minorities' Diminished Psychedelic Returns: Gender, Perceived Stigma, and Distress - Sean Matthew Viña (MDPI AG, 2024)
Because psychedelics have been found to increase psychological traits like openness, mental flexibility, and interpersonal perceptiveness, some researchers believe that psychedelics could help individuals cope with the psychological effects of discrimination. However, it is still unclear whether psychedelic use can help manage the internalized stigma that deters formal mental health treatment. This study investigates the impact of six measures of psychedelic use (MDMA, psilocybin, DMT, ayahuasca, peyote/mescaline, and LSD) on psychological distress (Kessler Psychological Distress Scale) and internalized stigma. The study used data from the National Survey of Drug Use and Health (NSDUH) from 2008 to 2019, with a sample size of 458,372 participants. Ordinary least square regression models were conducted using Stata 18. Gender analysis found that among men, ayahuasca use was linked to reduced stigma perception associated with higher distress. For women, DMT use was linked to reduced stigma perceptions when experiencing higher distress. However, results find that individuals who have used MDMA and psilocybin reported heightened perceptions of stigma associated with increased psychological distress. Among women, MDMA and psilocybin use was associated with a higher perception of stigma when they experienced distress. These findings suggest that, overall, psychedelics may not reduce the impact of distress on the perception of stigma, especially for women.